The vegetation of Holocene coastal dunes of the Cape south coast, South Africa - Richard M. Cowling; Hayley Cawthra; Sean Privett; B. Adriaan Grobler (PeerJ, 2023)
The vegetation of calcareous coastal dunes of Holocene age along the south coast of South Africa’s Cape Floristic Region is poorly described. This vegetation comprises a mosaic of communities associated with two biomes, Fynbos and Subtropical Thicket. Previously, expert knowledge rather than quantitative floristic analysis has been used to identify and delimit vegetation units. In many areas, mapped units conflate vegetation on Holocene sand with that on unconsolidated sediments of late Pleistocene age, despite pronounced species turnover across this edaphic boundary. Despite dominance by Cape lineages and fynbos vegetation, dune vegetation in the eastern part of the region has been included in the Subtropical Thicket Biome rather than the Fynbos Biome. The high levels of local plant endemism associated with this dune vegetation and the small and fragmented configuration of these habitats, makes it an urgent conservation priority especially when placed in the context of rising sea levels, increasing development pressures and numerous other threats. Here we provide a quantitative analysis of 253 plots of the 620 km2 of Holocene dune vegetation of the study area using phytosociological and multivariate methods. We identified six fynbos and two thicket communities based on the occurrences of 500 species. Following a long tradition in Cape vegetation typology, we used the Strandveld (beach vegetation) concept as our first-order vegetation entity and identified six units based on the fynbos floras. These were, from east to west, Southeastern Strandveld, St Francis Strandveld, Goukamma Strandveld, Southwestern Strandveld and Grootbos Strandveld. Each unit was differentiated by a suite of differential species, most being Holocene dune endemics. The two thicket communities—Mesic and Xeric Dune Thicket—showed limited variation across the study area and were subsumed into the Strandveld units. We discussed our findings in terms of vegetation–sediment relationships, emphasizing the need for a greater geographical coverage of sediment ages to facilitate a better understanding of deposition history on vegetation composition. We also discussed the role of soil moisture and fire regime on structuring the relative abundance of fynbos and thicket across the Holocene dune landscape. Finally, we address the conservation implications of our study, arguing that all remaining Holocene dune habitat should be afforded the highest conservation priority in regional land-use planning processes.